PESAN PROMOSI PROGRAM TELEVISI DALAM AKUN TWITTER @NETMEDIATAMA - Susanti, Santi; Erwina, Wina (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2020)
This study is entitled Promotion Messages on  the Twitter Account @netmediatama. The purpose of this research is to find out whether there is a relationship between the promotion of @netmediatama twitter accounts to the decision to watch NET. good people, namely the intensity of promotion, message content and message appeal. The method used in this study is a quantitative method with a correlational approach through primary questionnaire data. Data collection techniques are random sampling techniques from NET. Good People as many as 200 respondents. The results of this study indicate that there is a relationship with a moderate level between the intensity of program promotion through @ netmediatama account with the decision to watch, there is a low level between the contents of the program promotion message via twitter @netmediatama with the decision to watch and there is a moderate level between the attractiveness of program promotion through account @ netmediatama with the decision to watch in the form of feedback actions carried out by followers by the way of reply, retweet love promotion. NET program, clear information in tweets and the use of interesting and persuasive words between the promotion of @netmediatama's Twitter account (promotion intensity, message content appeal) to the NET Good People watching decision.